Laminated film
Patent Information
- Application Number
- JP2023500707
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-02-16
- Filing Date
- 2022-02-03
- Publication Date
- 2026-09-08
- Estimated Expiration
- 2042-02-03
AI Technical Summary
【0016】 本願発明によれば、ポリエステル樹脂を用いた基材フィルム層の上に、無機薄膜層及び保護層をこの順に有してなる積層フィルムとすることで、耐湿熱性や耐アルコール性や製膜回収性、さらにはバリア異方性に優れ、かつ、ラミネート積層体から積層フィルムとシーラント層を簡単に引き剥がすこともできるリサイクル性に優れた積層フィルムを提供することができるようになった。しかも、本発明の積層フィルムは印刷やラミネート等の加工工程においても、材料を選ばず、かつ広範囲の製造条件にて安定した品質を確保できるため、経済性と生産安定性の両方に優れており、均質な特性のガスバリア性フィルムを提供することができる。
Smart Images

Figure 0007916893000001 
Figure 0007916893000002
Abstract
Description
[Technical Field]
[0001] The present invention relates to a laminated film used in the packaging of food, pharmaceuticals, industrial products, etc. More specifically, it relates to a laminated film having an inorganic thin film layer and a protective layer in that order on a base film layer without a coating layer, which has excellent moisture and heat resistance, film recovery properties, and barrier anisotropy, and is also highly recyclable as the laminated film and sealant layer can be easily peeled off from the laminate. [Background technology]
[0002] Packaging materials used for food, pharmaceuticals, etc., are required to possess gas barrier properties—that is, properties that block gases such as oxygen and water vapor—in order to suppress the oxidation of proteins and fats, maintain taste and freshness, and preserve the efficacy of pharmaceuticals. Furthermore, gas barrier materials used in electronic devices and components such as solar cells and organic LEDs require even higher gas barrier properties than those used for food packaging materials.
[0003] Conventionally, in food applications requiring the barrier against various gases such as water vapor and oxygen, gas barrier laminates have been commonly used, which consist of a plastic base film with a metal thin film made of aluminum or the like, and an inorganic thin film made of inorganic oxides such as silicon dioxide or aluminum oxide, formed on its surface. Among these, those with a thin film (inorganic thin film layer) of inorganic oxides such as silicon dioxide, aluminum oxide, or mixtures thereof are widely used because they are transparent and allow for confirmation of the contents.
[0004] However, the aforementioned inorganic thin film layer is susceptible to physical and chemical damage from external sources, resulting in problems with reduced barrier performance and adhesion. To compensate for this performance degradation, it is common to either laminate a coating layer between the inorganic thin film layer and the substrate, or laminate a protective layer on top of the inorganic thin film layer. Regarding the former, for example, it has been reported that adhesion and water resistance can be improved by providing a coating layer made of an oxazoline group-containing water-soluble polymer between the substrate and the inorganic thin film layer (see, for example, Patent Document 1). On the other hand, for the latter, for example, a method can be described in which a water-soluble polymer, an inorganic layered compound, and a metal alkoxide or its hydrolysate are coated onto the inorganic thin film, and a highly crosslinked body of inorganic material containing the inorganic layered compound and a water-soluble polymer is formed on the inorganic thin film by the sol-gel method (see, for example, Patent Document 2). These methods can protect the vapor-deposited layer from external loads, and improvements in gas barrier performance can also be expected.
[0005] As mentioned above, by providing a coating layer, an inorganic thin film layer, and a protective layer as coating layers, it is possible to realize a gas barrier film that is resistant to external loads and maintains barrier properties and adhesion. However, gas barrier films consisting of a multilayer coating structure of dissimilar materials raise concerns about disadvantages from the perspective of promoting recycling and low environmental impact, which has become a subject of global discussion in recent years due to stricter regulations on reducing single-use plastics. For example, while lamination of coating layers with a cross-linked structure is very effective in achieving adhesive performance and water resistance, when attempting to recover and remelt and remake non-product portions of the base film made of thermoplastic resin during the film-making process, aggregates originating from the coating layer can become foreign matter and be mixed into the film, or in some cases, cause film breakage problems during film-making. Also, if aromatic compounds are used in the coating layer, the film may become discolored after remaking. The same can be said for the protective layer; for example, when a gas barrier film with polyvinylidene chloride laminated on an olefin film is recovered and melted, problems such as the generation of chlorine gas due to melting at high temperatures and difficulty in extrusion due to increased viscosity during extrusion occur. Even in the sol-gel method, there were problems such as the tendency for foreign matter to be generated depending on the degree of crosslinking.
[0006] Thus, until now, as long as performance was guaranteed, recyclability had not been particularly discussed. However, given the current situation where the problem of single-use plastic waste is becoming more serious, the inventors have found that in the future, product designs will need to give sufficient consideration to the recyclability of the laminated coating layers themselves.
[0007] Regarding environmental aspects, the inventors have found that sufficient consideration is necessary not only for the coating layer but also for the laminated structure. Generally, when gas barrier film is used as packaging bag, in addition to barrier properties and adhesion, the heat resistance of the base material itself, toughness (resistance to tearing and pinholes) depending on the contents, and sealing properties for packaging are also required. Gas barrier film alone cannot satisfy all of these performance requirements. For example, in packaging for retort products, it is common to have a configuration of two or more types of materials, such as a barrier polyester film on the outside of the bag, a polyamide film as an intermediate layer if necessary, and an olefin-based heat-sealable resin dry-laminated with adhesive on the inside (contents side). These laminated structures, composed of different materials, have high adhesion that allows them to withstand use, but when they become waste after use, it is difficult to peel and separate the materials. In this case, reuse as plastic (material recycling) is impossible, and conventionally, they have been disposed of by burning as thermal recycling. However, with the growing awareness of environmental issues in recent years, there is a desire for the realization of a single-material laminate structure, i.e., a monomaterial structure, that anticipates the possibility of recycling. For example, studies are being conducted to apply an inorganic thin film layer to a polyester sealant to achieve barrier performance and sealing properties in a single layer (see, for example, patent document). (See 3). However, with the current monomaterial configuration, it is not possible to meet all the required performance requirements. There was a difficult problem.
[0008] On the other hand, the quality requirements for barrier film packaging are becoming increasingly diverse. For example, boiling and retorting are common methods for sterilizing the contents of food packaging, but in recent years, hot packing (hot filling), which involves heating beverages to over 90°C, filling, and then cooling the container, is also being adopted to sterilize the contents inside the container. In this case, the film is instantaneously exposed to high temperature and humidity, so a barrier film with heat and humidity resistance is required even if it is not used for retorting. Furthermore, when used for non-food packaging applications such as disinfectants and cosmetics, a gas barrier film that is resistant to the alcohol and solvents in the contents is required. Generally, these resistances to humidity, heat, and solvents tend to improve by increasing the crosslinking density of the coating layer and suppressing the swelling and dissolution of the barrier layer itself. However, this presents a trade-off from the perspective of the ease of recovery of the coating layer, as mentioned above.
[0009] Furthermore, in recent years, there has been an increasing demand for barrier films to be anisotropic. For example, in the case of cosmetics and other applications mentioned above, water vapor barrier performance from the inside to the outside of the bag is important to prevent the loss of highly volatile contents. However, oxygen barrier performance generally prevents oxygen from permeating from the outside to the inside of the bag, and it is required that barrier performance be exhibited on both permeable surfaces. In contrast, polyvinyl alcohol, a common barrier resin, is highly dependent on humidity, and when exposed to a high-humidity environment (contents The barrier performance differs depending on whether the contents are liquid (inside the bag) or not (outside the bag). In other words, anisotropy occurs. The anisotropy problem can be improved by reducing the amount of hydrophilic groups in the barrier layer through a crosslinking reaction or by reducing the amount of hydrophilic groups added to reduce humidity dependence, but this was not always sufficient. Furthermore, crosslinking tended to worsen the absolute value of the barrier performance. Moreover, from the perspective of the ease of recovery of the coating layer mentioned above, the introduction of a crosslinked structure is undesirable.
[0010] Based on the above background, the inventors focused on a low-environmental-impact gas barrier film that has sufficient durability for its intended use, excellent barrier performance (especially anisotropy), is easily recoverable, and also has excellent recyclability as a laminate. [Prior art documents] [Patent Documents]
[0011] [Patent Document 1] Patent No. 5560708 [Patent Document 2] Japanese Patent Publication No. 2000-43182 [Patent Document 3] International Publication No. 2019 / 187970 [Overview of the project] [Problems that the invention aims to solve]
[0012] While Patent Documents 1 and 2 describe barrier performance and adhesion after retort processing, they do not consider the recyclability of the laminated film or the recyclability of the laminated body after use. Patent Document 3 does not consider durability against contents or recyclability. Patent Document 4 has insufficient barrier performance, and does not consider the anisotropy of the barrier or resistance to contents.
[0013] This invention was made against the backdrop of the problems of the prior art described above. In other words, the objective is to provide a laminated film having an inorganic thin film layer and a protective layer in that order on a base film layer made of polyester resin, which is excellent in moisture and heat resistance, alcohol resistance, film recovery, and barrier anisotropy, and is also highly recyclable, as the laminated film and sealant layer can be easily peeled off from the laminate. [Means for solving the problem]
[0014] The present inventors have enabled easy recoverability of a base film by using a polyester resin having no coating layer as the base material. By laminating a specific barrier protective layer on the inorganic thin film layer, a laminated film that is excellent in moist heat resistant adhesion and barrier anisotropy and also has alcohol resistance can be obtained even without a coating layer. Furthermore, the inventors have found that by utilizing the property that the adhesiveness of the protective layer decreases when boiled in boiling water for a certain period of time, the laminated film can be easily peeled off from the laminate, and thus completed the present invention.
[0015] That is, the present invention has the following constitution. (1) A laminated film having an inorganic thin film layer on at least one surface of a base film, and having a lay er of protective layer containing a urethane resin having a xylylene group on the inorganic thin film layer, wherein the laminated film satisfies the following requirements (a) to (d). (a) No coating layer is laminated between the base film and the inorganic thin film layer. (b) When water vapor permeates from the base film side through the protective layer under the condition of 40°C × 90% RH , the ratio A / B of the water vapor permeability A in this case to the water vapor permeability B when water vapor permeates from the protective layer side is 2.0 or less. (c) The peak intensity (P1) having an absorption maximum in the region of 1530±10cm-1 in the total reflection infrared absorption spectrum of the protective layer , and the ratio (P2 / P1) of the peak intensity (P1) to the peak intensity (P2) having an absorption maximum in the region of 1530±10cm-1 on the protective layer surface after the laminated film is immersed in 95°C hot water for 10 minutes, then a tape is adhered to the protective layer surface and peeled off, is 0.7 or more. (d) The peak intensity (P1) having an absorption maximum in the region of 1530±10cm-1 in the total reflection infrared absorption spectrum of the protective layer , and the ratio (P2 / P1) of the peak intensity (P1) to the peak intensity (P2) having an absorption maximum in the region of 1530±10cm-1 on the protective layer surface after the laminated film is immersed in 99% ethanol for 1 hour, then a tape is adhered to the protective layer surface and peeled off, is 0.7 or more. (2) The oxygen permeability of the laminated film at 23°C × 65%RH is 10 ml / m² 2 The laminated film according to (1), characterized in that it is less than or equal to d·MPa. (3) The laminated film according to (1) or (2), characterized in that the amount of metaxylylene groups in the urethane resin having metaxylylene groups contained in the protective layer is 12 to 33% by mass, and the amount of silanol groups is 700 to 1700 mg per 1 kg of resin constituting the polyurethane resin as the amount of Si element contained in the silanol groups. (4) The laminated film according to any one of (1) to (3), wherein the inorganic thin film layer is an aluminum oxide layer or a layer of a composite oxide of silicon oxide and aluminum oxide. (5) A laminated body obtained by laminating a sealant layer on one side of a laminated film as described in any of (1) to (4). (6) The laminated laminate according to (5), characterized in that the laminate strength after boiling sterilization of the laminated laminate in 90°C hot water for 2 hours is 0.5 N / 15 mm or less. [Effects of the Invention]
[0016] According to the present invention, by providing a laminated film having an inorganic thin film layer and a protective layer in that order on a base film layer made of polyester resin, it is possible to provide a laminated film that is excellent in moisture and heat resistance, alcohol resistance, film recovery, and barrier anisotropy, and is also highly recyclable as the laminated film and sealant layer can be easily peeled off from the laminated structure. Moreover, the laminated film of the present invention can ensure stable quality in a wide range of manufacturing conditions and is not limited by materials in processing processes such as printing and lamination, thus providing a gas barrier film with homogeneous properties that is excellent in both economy and production stability. [Modes for carrying out the invention]
[0017] The present invention will be described in detail below. [Base film] The base film used in the present invention (hereinafter sometimes referred to as "base film") may be, for example, a film obtained by melt-extruding plastic and, if necessary, stretching, cooling, and heat-setting it in the longitudinal and / or widthwise directions. Examples of plastics include polyamides represented by nylon 4-6, nylon 6, nylon 6-6, nylon 12, etc.; polyesters represented by polyethylene terephthalate, polybutylene terephthalate, polyethylene-2,6-naphthalate, etc.; polyolefins represented by polyethylene, polypropylene, polybutene, etc.; as well as polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, fully aromatic polyamide, polyamide-imide, polyimide, polyetherimide, polysulfone, polystyrene, polylactic acid, etc. Among these, polyester is preferred in terms of heat resistance, dimensional stability, and transparency, and polyethylene terephthalate and copolymers obtained by copolymerizing polyethylene terephthalate with other components are particularly preferred.
[0018] As the base film, any thickness can be used depending on the desired purpose and application, such as mechanical strength and transparency. The thickness is not particularly limited, but it is generally recommended to be between 5 and 250 μm, and when used as a packaging material, it is desirable to be between 10 and 60 μm. While there are no particular limitations on the transparency of the base film, when used as a packaging material where transparency is required, it is desirable to have a light transmittance of 50% or more.
[0019] The base film may be a single-layer film made of one type of plastic, or a laminated film made by laminating two or more types of plastic films. In the case of a laminated film, the type of laminate, the number of layers, the lamination method, etc., are not particularly limited and can be arbitrarily selected from known methods depending on the purpose. Furthermore, the base film may be subjected to surface treatments such as corona discharge treatment, glow discharge treatment, flame treatment, and surface roughening treatment, as long as it does not impair the objectives of the present invention, and may also be subjected to known anchor coating treatments, printing, decoration, etc.
[0020] The base film of this invention does not have a coating layer laminated onto it. As a result, the base material consists of a single material, making it possible to easily recover and reuse the film after it has been formed. If a coating layer is present, the recovered film may become discolored, foreign matter may be generated, or the film may break.
[0021] [Inorganic thin film layer] The gas barrier laminated film of the present invention has an inorganic thin film layer on the surface of the base film layer. The inorganic thin film layer is a thin film made of a metal or an inorganic oxide. The material forming the inorganic thin film layer is not particularly limited as long as it can be made into a thin film, but from the viewpoint of gas barrier properties, inorganic oxides such as silicon dioxide (silica), aluminum oxide (alumina), and mixtures of silicon dioxide and aluminum oxide are preferred. In this composite oxide, the mixing ratio of silicon dioxide and aluminum oxide is preferably in the range of 20 to 70% by mass of Al in terms of the mass ratio of the metal content. If the Al concentration is less than 20% by mass, the water vapor barrier properties may be low. On the other hand, if it exceeds 70% by mass, the inorganic thin film layer tends to harden, and there is a risk that the film will be destroyed during secondary processing such as printing or lamination, reducing the gas barrier properties. Also, when the Al concentration is 100% by mass, the water vapor barrier performance is good, but because it is a single material, the surface tends to be smooth, resulting in poor slipperiness and making it prone to processing defects (wrinkles, blemishes, etc.). In this context, silicon oxide refers to various silicon oxides such as SiO and SiO2, or mixtures thereof, while aluminum oxide refers to various aluminum oxides such as AlO and Al2O3, or mixtures thereof.
[0022] The thickness of the inorganic thin film layer is typically 1 to 100 nm, preferably 5 to 50 nm. If the thickness of the inorganic thin film layer is less than 1 nm, it may be difficult to obtain satisfactory gas barrier properties. On the other hand, if the thickness is excessively high, exceeding 100 nm, the corresponding improvement in gas barrier properties will not be obtained, and it may even be disadvantageous in terms of flexibility and manufacturing costs. Furthermore, from the standpoint of recyclability, if the film thickness is too high, it may adversely affect subsequent recovery processes.
[0023] There are no particular restrictions on the method for forming an inorganic thin film layer; for example, any known deposition method such as vacuum deposition, sputtering, ion plating (physical vapor deposition methods (PVD)), or chemical vapor deposition (CVD) can be used as appropriate. Below, a typical method for forming an inorganic thin film layer will be described using a silicon oxide / aluminum oxide thin film as an example. For example, when using vacuum deposition, a mixture of SiO2 and Al2O3, or a mixture of SiO2 and Al, is preferably used as the deposition raw material. These deposition raw materials are usually particles, and it is desirable that the size of each particle is such that the pressure during deposition does not change, with a preferred particle size of 1 mm to 5 mm. For heating, methods such as resistance heating, high-frequency induction heating, electron beam heating, and laser heating can be used. It is also possible to use reactive deposition by introducing oxygen, nitrogen, hydrogen, argon, carbon dioxide, water vapor, etc. as a reaction gas, or by using means such as ozone addition or ion assistance. Furthermore, the film formation conditions can be arbitrarily changed, such as by applying a bias to the substrate (laminated film to be deposited) or by heating or cooling the substrate. These deposition materials, reaction gases, bias of the material to be deposited, heating / cooling, etc., can be similarly modified when using sputtering or CVD methods.
[0024] [Protective layer] In this invention, a protective layer is provided on the inorganic thin film layer. The metal oxide layer is not a completely dense film, but has minute defects scattered throughout. By coating the metal oxide layer with a specific protective resin composition described later to form a protective layer, the resin in the protective resin composition penetrates into the defects in the metal oxide layer, resulting in improved gas barrier properties and enhanced adhesion between the substrate, the inorganic thin film layer, and the protective layer. In addition, by using a material with gas barrier properties for the protective layer itself, the gas barrier performance of the laminated film is also greatly improved.
[0025] The protective layer of the present invention comprises a polyurethane resin having metaxylylene groups. The metaxylylene group content in the polyurethane resin is preferably in the range of 12 to 33% by mass. A metaxylylene group content of 12% by mass or more allows for good gas barrier properties to be achieved. Furthermore, it is preferable that the polyurethane resin contains silanol groups, in which case the amount of silanol groups is 700 to 1700 mg per kg of the polyurethane resin, as the amount of Si element contained in the silanol groups. In addition, having the amount of silanol groups in the above range provides good interfacial adhesion with the metal oxide layer, which is an inorganic thin film. Furthermore, because the resin itself retains flexibility, it has excellent stress-relieving ability and can maintain adhesion to the substrate even without a coating layer. Moreover, by promoting partial self-crosslinking by the silanol groups, a film that is less prone to swelling in alcohol or water can be made, thus avoiding a decrease in the adhesion of the protective layer due to immersion in hot water or alcohol. Furthermore, because it has a partially cross-linked structure, the adhesive strength decreases when subjected to hot water treatment for a certain period of time or longer, allowing the film to be easily peeled off the laminate, resulting in a film with excellent recyclability.
[0026] Next, the components of the protective layer resin composition that forms the protective layer will be described in detail. (Polyurethane resin (E)) The polyurethane resin (E) dispersion of the present invention (hereinafter referred to as polyurethane resin (E)-containing dispersion) is obtained by dispersing a polyurethane resin (aqueous polyurethane resin) in water, and the polyurethane resin is obtained by the reaction of an isocyanate group-terminated prepolymer with a chain extender. Isocyanate-terminated prepolymers are obtained by the reaction of a polyisocyanate component with a polyol component.
[0027] Polyisocyanate components contain xylylene diisocyanate as an essential component. Structural isomers of xylylene diisocyanate (XDI) include 1,2-xylylene diisocyanate (o-XDI), 1,3-xylylene diisocyanate (m-XDI), and 1,4-xylylene diisocyanate (p-XDI). These xylylene diisocyanates can be used alone or in combination of two or more types. Preferred xylylene diisocyanates include 1,3-xylylene diisocyanate, 1,4-xylylene diisocyanate, and more preferably 1,3-xylylene diisocyanate. By including xylylene groups, particularly 1,3-xylylene groups (metaxylylene groups), high gas barrier properties can be achieved. As mentioned above, the metaxylylene group content in polyurethane resin (E) is 12 to 33% by mass, and by keeping the metaxylylene group content within this range, a good balance between gas barrier properties and the flexibility of polyurethane resin (E) can be maintained. This is possible. The metaxylylene group content is more preferably 14 to 32% by mass, and particularly preferably 16 to 32% by mass.
[0028] Furthermore, the polyisocyanate component may also contain other polyisocyanates as needed. Examples of other polyisocyanates include tolylene diisocyanate (2,4- or 2,6-tolylene diisocyanate or a mixture thereof) (TDI), phenylene diisocyanate (m-, p-phenylene diisocyanate or a mixture thereof), 1,5-naphthalene diisocyanate (NDI), diphenylmethane diisocyanate (4,4'-, 2,4'- or 2,2'-diphenylmethane diisocyanate or a mixture thereof) (MDI), tetramethylxylylene diisocyanate (1,3- or 1,4-tetramethylxylylene diisocyanate or a mixture thereof) (TMXDI), and 1,6-hexamethylene diisocyanate. Examples include hexamethylene diisocyanate (HDI), hydrogenated xylylene diisocyanate (bis(isocyanatomethyl)cyclohexane) (H6XDI), 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate (isophorone diisocyanate) (IPDI), methylenebis(cyclohexyl isocyanate) (bis(isocyanatocyclohexyl)methane) (4,4'-, 2,4'- or 2,2'-methylenebis(cyclohexyl isocyanate), their trans,trans-, trans,Cis-, Cis,Cis-, or mixtures thereof) (H12MDI). These other polyisocyanates can be used alone or in combination of two or more types. Preferably, aromatic aliphatic polyisocyanates and alicyclic polyisocyanates are used, and more preferably, alicyclic polyisocyanates are used.
[0029] The polyol component includes, as essential components, diols with 2 to 6 carbon atoms and polyols containing carboxyl groups. C2-C6 diols are organic compounds having two hydroxyl groups and containing two carbon atoms. Specifically, examples include C2-C6 alkanediols (C2-C6 alkylene glycols) such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butylene glycol, 1,3-butylene glycol, 1,2-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, and 1,3- or 1,4-cyclohexanediol, as well as C2-C6 ether diols such as diethylene glycol, triethylene glycol, and dipropylene glycol.
[0030] These diols with 2 to 6 carbon atoms can be used individually or in combination of two or more types. Examples of diols having 2 to 6 carbon atoms include, preferably, alkanediols having 2 to 6 carbon atoms, and more preferably, ethylene glycol. Examples of carboxyl group-containing polyols include polyhydroxyalkano acids such as 2,2-dimethylolacetic acid, 2,2-dimethylollactic acid, 2,2-dimethylolpropionic acid (also known as dimethylolpropionic acid), 2,2-dimethylolbutanoic acid, 2,2-dimethylolbutyric acid, and 2,2-dimethylolvaleric acid, with 2,2-dimethylolpropionic acid being preferred. Furthermore, the polyol component may also contain other polyol compounds (excluding the C2-C6 diols and carboxyl group-containing polyols mentioned above) as optional components.
[0031] Other polyol compounds include, for example, low molecular weight polyols with a valent or higher nucleotide, such as trimethylolpropane and glycerin, as well as polyether polyols, polyester polyols, polycarbonate polyols, polycaprolactone polyols, polyolefin polyols, and acrylic polyols. These polyol compounds (excluding the diols with 2 to 6 carbon atoms and polyols containing carboxyl groups mentioned above) can be used individually or in combination of two or more types. The polyhydroxyalkanoic acid is preferably blended so that the acid value of the resin solids is 5 to 40 mg KOH / g, more preferably 10 to 30 mg KOH / g, and even more preferably 15 to 25 mg KOH / g.
[0032] To synthesize an isocyanate-terminated prepolymer, each of the above components is blended in an equivalent ratio of isocyanate groups to active hydrogen groups (hydroxyl groups and amino groups) (isocyanate groups / active hydrogen groups) that is greater than 1, preferably 1.1 to 10. Then, the above components are reacted using a known polymerization method such as bulk polymerization or solution polymerization, preferably solution polymerization, which allows for easier adjustment of reactivity and viscosity. In bulk polymerization, for example, the above components are mixed under a nitrogen atmosphere and reacted at a reaction temperature of 75-85°C for about 1-20 hours.
[0033] In solution polymerization, for example, the above components are mixed with an organic solvent (solvent) under a nitrogen atmosphere and reacted at a reaction temperature of 20-80°C for about 1-20 hours. Examples of organic solvents that are inert to isocyanate groups and highly hydrophilic include acetone, methyl ethyl ketone, ethyl acetate, tetrahydrofuran, and acetonitrile. Furthermore, in the polymerization described above, reaction catalysts such as amine-based, tin-based, or lead-based catalysts may be added as needed.
[0034] Furthermore, if an anionic group is present, for example, a neutralizing agent is preferably added to neutralize it and form a salt of the anionic group. Examples of neutralizing agents include conventional bases, such as organic bases (e.g., tertiary amines (trialkylamines with 1-4 carbon atoms such as trimethylamine and triethylamine, alkanolamines such as dimethylethanolamine, methyldiethanolamine, triethanolamine, and triisopropanolamine)) and inorganic bases (ammonia, alkali metal hydroxides (lithium hydroxide, sodium hydroxide, potassium hydroxide, etc.), alkaline earth metal hydroxides (magnesium hydroxide, calcium hydroxide, etc.), and alkali metal carbonates (sodium carbonate, potassium carbonate, etc.)). These bases can be used individually or in combination of two or more types.
[0035] The neutralizing agent is added in an amount of 0.4 equivalents or more, preferably 0.6 equivalents or more, per equivalent of anionic group, and also in an amount of, for example, 1.2 equivalents or less, preferably 1 equivalent or less. The isocyanate-terminated prepolymer obtained in this manner is a polyurethane prepolymer having two or more free isocyanate groups at its molecular termini, wherein the isocyanate group content (isocyanate group content on a solid content basis excluding solvent) is, for example, 1.0% by mass or more and 10% by mass or less.
[0036] Next, in this method, the isocyanate group-terminated prepolymer obtained above is reacted with a chain extender, for example, in water, to obtain a polyurethane resin-containing dispersion. The chain extender contains an alkoxysilyl compound having an amino group as an essential component. Examples of alkoxysilyl compounds having an amino group include N-β(aminoethyl)γ-aminopropyltrimethoxysilane (also known as N-2-(aminoethyl)-3-aminopropyltrimethoxysilane), N-β(aminoethyl)γ-aminopropyltriethoxysilane (also known as N-2-(aminoethyl)-3-aminopropyltriethoxysilane), N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane (also known as N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane), and N-β(aminoethyl)γ-aminopropylmethyldiethoxysilane (also known as N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane). These alkoxysilyl compounds containing amino groups can be used individually or in combination of two or more types.
[0037] Furthermore, the chain extension agent may optionally include other polyamines (excluding alkoxysilyl compounds having an amino group) as an optional component, as long as it does not impair the excellent effects of the present invention. Other polyamines include, for example, 4,4'-diphenylmethanediamine, 1,3- or 1,4-xylylenediamine or mixtures thereof, 3-aminomethyl-3,5,5-trimethylcyclohexylamine (also known as isophoronediamine), 4,4'-dicyclohexylmethanediamine, 1,3- and 1,4-bis(aminomethyl)cyclohexane and mixtures thereof, ethylenediamine, 1,6-hexamethylenediamine, hydrazine (including hydrate), 2-((2-aminoethyl)amino)ethanol (also known as N-(2-aminoethyl)ethanolamine), and 2-((2-aminoethyl)amino)-1-methylpropanol (also known as N-(2-aminoethyl)isopropanolamine). These other polyamines can be used individually or in combination of two or more. Examples of other polyamines include amino alcohols.
[0038] Furthermore, the chain elongator preferably consists of an alkoxysilyl compound having an amino group and an amino alcohol. The amount of alkoxysilyl compound having an amino group is preferably in the range of 700 to 1700 mg of Si content per 1 kg of resin solids, more preferably 900 to 1500 mg, and even more preferably 1100 to 1300 mg.
[0039] To react the isocyanate-terminated prepolymer with a chain extender in water, for example, first, the isocyanate-terminated prepolymer is dispersed in water by adding it to the water, and then the chain extender is added to the water to extend the chain of the isocyanate-terminated prepolymer with the chain extender. To disperse the isocyanate-terminated prepolymer in water, add the isocyanate-terminated prepolymer in a ratio of 100 to 1000 parts by mass of water to 100 parts by mass of isocyanate-terminated prepolymer, while stirring the water. Subsequently, the chain extender is added dropwise to the aqueous dispersion of the isocyanate-terminated prepolymer under stirring, so that the equivalent ratio of the active hydrogen groups (amino groups and hydroxyl groups) of the chain extender to the isocyanate groups of the isocyanate-terminated prepolymer (active hydrogen groups / isocyanate groups) is, for example, 0.6 to 1.2.
[0040] The chain extender is added dropwise to initiate the reaction, and after the addition is complete, the reaction is allowed to complete, for example, at room temperature, while continuing to stir. The reaction time until completion is, for example, 0.1 hours or more, and for example, 10 hours or less. Furthermore, this method allows for the removal of organic solvents and water as needed, and even the addition of water to adjust the solid content concentration. The solid content concentration of the resulting polyurethane resin-containing dispersion is, for example, 10% by mass or more, preferably 15% by mass or more, more preferably 20% by mass or more, and also, for example, 60% by mass or less, preferably 50% by mass or less, more preferably 45% by mass or less.
[0041] One known method for introducing silanol groups into the protective layer is to add silane coupling agents after the fact. However, in this invention, we have found that introducing silanol groups into the urethane resin skeleton has a greater effect on barrier properties and adhesion than the post-addition method. Furthermore, the post-addition method increases the complexity of the work and increases the possibility of errors in measuring the amount added. On the other hand, by pre-containing silanol groups in the polyurethane dispersion skeleton, the aforementioned complexity and errors can be prevented.
[0042] If the amount of silanol groups contained in polyurethane resin (E) is less than 700 mg per kg of the resin constituting the polyurethane resin (E) as the amount of Si element contained in the silanol groups, the crosslinked structure Insufficient formation of the structure leads to a decrease in water-resistant adhesion and gas barrier properties. Furthermore, swelling in response to alcohol is also insufficient. Furthermore, if the amount of silanol groups contained exceeds 1700 mg per kg of resin that constitutes the polyurethane resin (E), the number of cross-linked structures becomes excessive, impairing the flexibility of the protective layer and leading to deterioration of the metal oxide layer and a decrease in flexural resistance. Moreover, there is a risk that this film will easily form aggregates when collected and recycled.
[0043] When forming a protective layer using a protective resin composition, a coating solution (coating liquid) consisting of the polyurethane resin, ion-exchanged water, and a water-soluble organic solvent is prepared, applied, and dried. As the water-soluble organic solvent, a single or mixed solvent can be selected from alcohols such as ethanol and isopropyl alcohol (IPA), or ketones such as acetone and methyl ethyl ketone. From the viewpoint of coating film processing and odor, IPA is preferred.
[0044] The coating method for the protective layer resin composition is not particularly limited as long as it is a method of coating the film surface to form a layer. For example, conventional coating methods such as gravure coating, reverse roll coating, wire bar coating, and die coating can be used.
[0045] The amount of protective layer resin composition applied is not particularly limited, but it is preferably in the range of 0.05 to 1.0 g / m2 in a dry state, and from a practical standpoint, 0.10 to 0 A range of 0.50 g / m² is more preferable, and even more preferable is 0.15 to 0.35 g / m². The answer is 2. If the concentration is less than 0.05 g / m2, sufficient adhesion, gas barrier properties, and protective effect can be obtained. It becomes more difficult to obtain, and at concentrations above 1.0 g / m2, it tends to be cost-ineffective.
[0046] When forming the protective layer, it is preferable to apply the protective layer resin composition and then heat-dry it, with a preferred drying temperature of 110 to 210°C, more preferably 120 to 200°C, and even more preferably 130 to 190°C. If the drying temperature is below 110°C, the protective layer may not dry sufficiently, or the crosslinking of the protective layer may not proceed, resulting in reduced adhesion. On the other hand, if the drying temperature exceeds 210°C, the film may be overheated, making it brittle or shrinking, which may impair its processability. It is particularly preferable to first evaporate the solvent at a relatively low temperature of 90°C to 110°C immediately after application, and then dry the protective film at 150°C or higher, as this yields a uniform film. In addition to drying, applying an additional heat treatment in the lowest possible temperature range is also effective in promoting the crosslinking of the protective layer.
[0047] [Packaging materials] In the laminated structure of the present invention, it is necessary to use a heat-sealable resin layer called a sealant layer. The heat-sealable resin layer is usually provided on an inorganic thin film layer, but it may also be provided on the outside of the base film layer (the side opposite the surface where the coating layer is formed). The heat-sealable resin layer is usually formed by extrusion lamination or dry lamination. The thermoplastic polymer used to form the heat-sealable resin layer can be any polymer that exhibits sufficient sealant adhesion, such as polyethylene resins like HDPE, LDPE, and LLDPE, polypropylene resin, ethylene-vinyl acetate copolymer, ethylene-α-olefin random copolymer, and ionomer resin. Among these, LLDPE or polypropylene resin are particularly preferred due to their high versatility in terms of durability, seal strength, and cost. The thickness is preferably 20 to 100 μm, more preferably 30 to 90 μm, and more preferably 40 to 80 μm. If the thickness is less than 20 μm, sufficient seal strength may not be obtained, and the material may lack stiffness and be difficult to handle. On the other hand, if the thickness exceeds 100 μm, the material becomes too stiff, reducing its handling as a bag, and the price may also increase.
[0048] [Adhesive layer] The adhesive layer used in this invention can be any general-purpose laminating adhesive. For example, solvent-free, water-based, or heat-melt adhesives mainly composed of poly(ester)urethane, polyester, polyamide, epoxy, poly(meth)acrylic, polyethyleneimine, ethylene-(meth)acrylic acid, polyvinyl acetate, (modified) polyolefin, polybutadiene, wax, or casein can be used. Among these, urethane or polyester adhesives are preferred considering their resistance to humid heat that can withstand retort treatment and their flexibility to follow dimensional changes of each substrate. The adhesive layer can be applied by methods such as direct gravure coating, reverse gravure coating, kiss coating, die coating, roll coating, dip coating, knife coating, spray coating, fontein coating, and others, and sufficient adhesion is achieved even after humid heat treatment, so the coating amount after drying is 1 to 8 g / m². 2 Preferred. More preferably 2-7 g / m 2 More preferably 3-6 g / m 2 The coating amount is 1 g / m². 2 If the amount is less than 8 g / m², it becomes difficult to bond the entire surface, and the adhesive strength decreases. 2 Beyond this point, complete curing of the film takes longer, unreacted material is more likely to remain, and the adhesive strength decreases.
[0049] Furthermore, the laminated film of the present invention may have at least one printed layer or other plastic substrate and / or paper substrate laminated between or outside the inorganic thin film layer or substrate film layer and the heat-sealable resin layer.
[0050] As the printing ink for forming the printed layer, aqueous and solvent-based resin-containing printing inks can be preferably used. Examples of the resin used in the printing ink herein include acrylic resins, urethane resins, polyester resins, vinyl chloride resins, vinyl acetate copolymer resins, and mixtures thereof. The printing ink may contain known additives such as antistatic agents, light blocking agents, ultraviolet absorbers, plasticizers, lubricants, fillers, colorants, stabilizers, lubricants, defoamers, crosslinking agents, antiblocking agents, and antioxidants. The printing method for providing the printed layer is not particularly limited, and known printing methods such as offset printing, gravure printing, and screen printing can be used. For drying the solvent after printing, known drying methods such as hot air drying, hot roll drying, and infrared drying can be used.
[0051] The laminate of the present invention has an oxygen permeability of 10 ml / m 2 ·d·MPa or less under conditions of 23° C. and 65% RH, which is preferable from the viewpoint of exhibiting good gas barrier properties. Furthermore, by controlling the components and adhesion amount of the aforementioned inorganic thin film layer, the oxygen permeability is preferably 9 ml / m 2 ·d·MPa or less, more preferably 8 ml / m 2 ·d·MPa or less. If the oxygen permeability exceeds 10 ml / m 2 ·d·MPa, it becomes difficult to adapt the laminate to applications requiring high gas barrier properties. On the other hand, if the oxygen permeability both before and after retort treatment is less than 1 ml / m 2 ·d·MPa, although the barrier performance is excellent, the residual solvent is less likely to permeate to the outside of the bag, which may relatively increase the amount transferred to the contents, and thus this is not preferable. The preferable lower limit of the oxygen permeability is 1 ml / m 2 ·d·MPa or more.
[0052] The laminated film of the present invention has a water vapor transmission rate of 1.5 g / m 2 ·d or less under conditions of 40° C. and 90% RH regardless of the transmission direction, which is preferable from the viewpoint of exhibiting good gas barrier properties. Furthermore, by controlling the components and adhesion amount of the aforementioned inorganic thin film layer, the water vapor transmission rate is preferably 1.2 g / m 2 ·d or less, more preferably 1.0 g / m 2It can be less than or equal to d. Water vapor transmission rate of 1.5 g / m³ 2 If the value exceeds d, it becomes difficult to meet the requirements for applications that demand high gas barrier properties. On the other hand, if the water vapor transmission rate is 0.1 g / m³ 2 If the value is less than 0.1 g / m³, while the barrier performance is excellent, residual solvent will not easily permeate to the outside of the bag, which may relatively increase the amount transferred to the contents, so this is undesirable. The preferred lower limit for water vapor permeability is 0.1 g / m³. 2 It is d or higher.
[0053] In the laminated film of the present invention, it is preferable that the ratio B / A of the water vapor permeability B when water vapor permeates from the protective layer side to the water vapor permeability A when water vapor permeates from the base film side is 2.0 or less under 40°C × 90%RH conditions. By keeping it within this range, the anisotropy of the barrier is reduced, and barrier performance can be exhibited on either side. More preferably, it is 1.8 or less, and even more preferably 1.6 or less. If the above range exceeds 2.0, an imbalance in barrier performance may occur, and depending on the application, the protection of the contents may not be sufficient.
[0054] The laminated film of the present invention is characterized in that the ratio (P2 / P1) of the peak intensity (P1) with an absorption maximum in the region of 1530±10cm-1 in the total reflection infrared absorption spectrum of the protective layer to the peak intensity (P2) with an absorption maximum in the region of 1530±10cm-1 on the surface of the protective layer after immersion of the laminated film in 95°C hot water for 10 minutes, followed by application and removal of tape from the surface of the protective layer, is 0.7 or higher. The peak at 1530±10cm-1 is the peak of NH bending vibration originating from the urethane group and serves as an indicator of the amount of urethane or urea bond in the protective layer. The larger this peak ratio (P2 / P1) is, the more urethane component in the protective layer remains on the film even after moist heat treatment, meaning that the protective layer has excellent moist heat resistance. This characteristic provides practical moist heat resistance, expanding the range of applications in which it can be used. The preferred range for the peak ratio (P2 / P1) is 0.75 or higher, more preferably 0.8 or higher, and even more preferably 0.85 or higher. If the peak ratio is less than 0.7, the adhesive strength of the protective layer may decrease during moist heat treatment such as hot packing, potentially leading to delamination or deterioration of gas barrier properties.
[0055] The laminated film of the present invention has a ratio (P2 / P) between the peak intensity (P1) with an absorption maximum in the region of 1530±10cm-1 in the total reflection infrared absorption spectrum of the protective layer and the peak intensity (P2) with an absorption maximum in the region of 1530±10cm-1 on the surface of the protective layer after immersing the laminated film in 99% ethanol for 1 hour, then applying and peeling off tape from the surface of the protective layer. 1) is characterized by being 0.7 or higher. The larger this peak ratio (P2 / P1), the higher the humidity. Even after heat treatment, a large amount of the urethane component in the protective layer remains on the film, meaning that the protective layer has excellent solvent resistance. This characteristic provides practical solvent resistance, expanding the range of applications in which it can be used. The preferred range for the peak ratio (P2 / P1) is 0.75 or higher, more preferably 0.8 or higher, and even more preferably 0.85 or higher. If the peak ratio is less than 0.7, the adhesive strength of the protective layer may decrease when filled and stored with ethanol as the contents, potentially leading to delamination or deterioration of gas barrier properties.
[0056] The laminated materials of the present invention preferably have a laminate strength of 1.0 N / 15 mm or more under 23°C × 65% RH conditions, more preferably 1.2 N / 15 mm or more, and even more preferably 1.5 N / 15 mm or more. If the laminate strength is less than 1.0 N / 15 mm, delamination may occur due to bending loads, etc., potentially leading to deterioration of barrier properties or leakage of contents. Furthermore, tearability may also be impaired.
[0057] The laminated material of the present invention preferably has a laminate strength of 1.0 N / 15 mm or less after immersion in 95°C hot water for 2 hours, more preferably 0.9 N / 15 mm or less, and even more preferably 0.8 N / 15 mm or less. If the laminate strength exceeds 1.0 N / 15 mm, it becomes difficult to easily peel off the laminated material, raising concerns about poor recyclability. Furthermore, increasing the temperature or lengthening the immersion time can be expected to further reduce the laminate strength, making it easier to peel off.
[0058] The preferred immersion treatment time for peeling the laminate in the present invention is 1 to 4 hours. More preferably, it is 1.5 to 3.5 hours, and even more preferably 2 to 3 hours. If the immersion time is less than 1 hour, the hot water may not penetrate the laminate sufficiently, and it may not be easy to peel it off. On the other hand, if it exceeds 4 hours, the treatment time becomes too long, and it may not be an effective method in terms of efficiency.
[0059] Based on the above, the laminated film of the present invention provides a film that is excellent in moisture and heat resistance, alcohol resistance, film recovery, and barrier anisotropy, and is also highly recyclable, as the laminated film and sealant layer can be easily peeled off from the laminate. [Examples]
[0060] Next, the present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples. The films were evaluated by the following measurement method.
[0061] (1) Intrinsic viscosity of the raw material resin and the resin constituting the film (IV) The sample was vacuum-dried at 130°C overnight, then pulverized or cut. 80 mg was accurately weighed and dissolved in a phenol / tetrachloroethane mixed solution of 60 / 40 (volume ratio) at 80°C for 30 minutes. After dissolving at 80°C, the mixture was cooled to room temperature, and the mixed solvent prepared in the aforementioned ratio in a volumetric flask was added to make a total volume of 20 ml. The viscosity was then measured at 30°C (unit: dl / g). An Ostwald viscometer was used to measure the intrinsic viscosity.
[0062] (2) Content of terephthalic acid and isophthalic acid components contained in the raw polyester and the polyester constituting the film A sample solution was prepared by dissolving the raw polyester resin or polyester film in a solvent prepared by mixing chloroform D (manufactured by Eurysop) and trifluoroacetic acid D1 (manufactured by Eurysop) in a 10:1 volume ratio. Subsequently, the proton NMR of the prepared sample solution was measured using an NMR spectrometer (Varian GEMINI-200) at a temperature of 23°C and with 64 integration cycles. In the NMR measurement, the peak intensity of a predetermined proton was calculated to determine the content (mol%) of terephthalic acid and isophthalic acid components in 100 mol% of the acid component.
[0063] (3) Thickness of the base film Measurements were taken using a dial gauge in accordance with JIS K7130-1999 Method A.
[0064] (4) Recovery of the base film (observation of appearance after re-film formation) The obtained base film was crushed and melted into chips at approximately 300°C using an extruder. Next, a film was created by forming a film using the obtained chips. The coloration and presence of foreign matter of this film were compared with the base film before film formation (without a coating layer) to evaluate its recoverability. ○: The coloring is the same as the film before recall and there are no foreign objects. △: The film is slightly discolored or contains some foreign matter. ×: The film is highly colored or contains a large amount of foreign matter, making it unsuitable for practical use.
[0065] (5) Composition and film thickness of inorganic thin film layer The film thickness composition of the laminated films (after thin film lamination) obtained in the examples and comparative examples was measured using a fluorescent X-ray analyzer (Rigaku Corporation's "ZSX100e") according to a pre-prepared calibration curve. The excitation X-ray tube conditions were set to 50kV and 70mA.
[0066] (6) Amount of coating / protective layer attached In each example and comparative example, the laminated films obtained at the stage of laminating the coating layer and protective layer onto the base film were used as samples. A 100 mm x 100 mm test piece was cut from this sample, and the coating layer and protective layer were wiped off with dimethylformamide. The amount of adhesion was calculated from the change in mass of the film before and after wiping.
[0067] (7) Method for measuring the total internal reflection infrared absorption spectrum of the protective layer In each example and comparative example, the total internal reflection infrared absorption spectrum was measured on the protective layer surface of each laminated film obtained after lamination of the protective layer onto the base film using total internal reflection infrared spectroscopy. Peak intensity A, with an absorption maximum in the region of 1530±10cm-1, and peak intensity B, with an absorption maximum in the region of 1410±10cm-1, were determined, and the ratio of these intensities (A / B) was calculated as peak intensity P1. Peak intensity B at 1410±10cm-1 is a peak originating from the polyester base film and was used as a reference peak for intensity quantification. Each peak intensity was calculated from the peak height drawn by vertically connecting the baseline (absorbance zero) and each peak top. Similar measurements were performed after the tape peel test described later, and the peak intensity P2 was calculated. Then, P2 / P1 was determined.
[0068] (Measurement conditions) Device: Bruker Optics "ALPHA ECO-ATR" Optical crystal: Ge Incident angle: 45° Resolution: 8cm-1 Total number of times: 64
[0069] (8) Tape peel test after immersion in hot water In each example and comparative example, the laminated film obtained at the stage of laminating a protective layer onto the base film was used as the sample. A 50 mm x 50 mm test piece was cut from this sample and immersed in 95°C hot water for 10 minutes using a water bath. After that, the sample was removed and the moisture on the film was wiped off with a Kimwipe, and then cellophane tape was applied to the protective layer side of the sample. After applying 20mm of Oji Tack (12mm wide, red) and pressing it firmly with your hands, one side The film was held down with one hand, and the tape was forcefully pulled upwards at a 90° angle with the other hand. The total infrared absorption spectrum measurement described above was performed on the sample surface after peeling. In addition, as a qualitative evaluation, the sample surface after peeling was visually observed and evaluated as follows: samples where more than 90% of the protective layer was peeled off were marked with ×, samples where 30-50% was peeled off were marked with △, and samples where no peeling occurred were marked with ○.
[0070] (9) Tape peel test after ethanol immersion In each example and comparative example, the laminated film obtained at the stage of laminating a protective layer onto the base film was used as the sample. A 50 mm x 50 mm test piece was cut from this sample, and the sample was placed in a glass bottle containing 99% ethanol and immersed for 1 hour at 23°C x 65% RH atmosphere. The sample was subjected to a soaking treatment. After that, the sample was removed, and the ethanol on the film was wiped off with a Kimwipe. Then, a 20mm length of cellophane tape (Oji Tack Co., Ltd., 12mm wide, red) was applied to the protective layer side of the sample and firmly pressed into place by hand. The film was then held down with one hand, and the tape was forcefully peeled off at a 90° angle with the other hand. The total infrared absorption spectrum measurement described above was performed on the sample surface after peeling. In addition, as a qualitative evaluation, the sample surface after peeling was visually observed and evaluated as follows: samples where more than 90% of the protective layer was peeled off the tape application area were marked with ×, samples where 30-50% was peeled off were marked with △, and samples where no peeling occurred were marked with ○.
[0071] (10) Method for evaluating oxygen permeability For the laminated films obtained in the examples and comparative examples, the oxygen permeability under normal conditions was measured using an oxygen permeability measuring device (MOCON's "OX-TRAN(registered trademark) 1 / 50") in accordance with JIS-K7126 Method B, under an atmosphere of 23°C and 65% RH. The oxygen permeability was measured in the direction in which oxygen permeates from the base film side to the protective layer side.
[0072] (11) Method for evaluating water vapor transmission For the laminated films obtained in the examples and comparative examples, the water vapor transmission rate under normal conditions was measured using a water vapor transmission rate measuring device (MOCON "PERMATRAN-W 3 / 33MG") in accordance with JIS-K7129 Method B, under an atmosphere of 40°C and 90% RH. The water vapor transmission rate was measured in either the direction in which water vapor permeates from the protective layer to the base film side or from the base film side to the protective layer side.
[0073] [Fabrication of laminated structures] A polyurethane adhesive (TM569 / cat10L, manufactured by Toyo Morton Co., Ltd.) was applied to the protective layer surface of the laminated films obtained in the Examples and Comparative Examples to a thickness of 3 μm after drying at 80°C. Then, an unstretched polypropylene film (P1128, manufactured by Toyobo; 30 μm thick; referred to as CPP) was dry-laminated on a metal roll heated to 60°C, and aged at 40°C for 4 days to obtain a laminate gas barrier laminate for evaluation (hereinafter sometimes referred to as "laminated laminate").
[0074] (12) Method for evaluating laminate strength The laminated material prepared as described above was cut into 15 mm wide and 200 mm long specimens to form test pieces. The laminate strength (before treatment) was measured using a Tensilon universal material tester (Tensilon UMT-II-500 model, manufactured by Toyo Baldwin Co., Ltd.) under conditions of 23°C and 65% relative humidity. The laminate strength was measured when the laminated film layer and the heat-sealable resin layer of each laminated film obtained in the examples and comparative examples were peeled at a peeling angle of 90 degrees with a tensile speed of 200 mm / min.
[0075] (13) Method for evaluating laminate strength after hot water immersion The laminated material prepared as described above was subjected to a moist heat treatment by being held in 95°C hot water for 2 hours. While still undried, it was cut into 15mm wide and 200mm long test pieces. The laminate strength (after moist heat treatment retort) was measured using a Tensilon universal material tester (Tensilon UMT-II-500 model, manufactured by Toyo Baldwin Co., Ltd.) under conditions of 23°C and 65% relative humidity. The laminate strength was defined as the strength when peeled at a peel angle of 90 degrees with a tensile speed of 200 mm / min and water applied between the laminated film and the heat-sealable resin layer.
[0076] (14) Evaluation of ease of peeling When the laminated structure immersed under the conditions of (12) above was peeled off, those that could be easily peeled off by hand were marked with ○, and those that could not be peeled off were marked with ×.
[0077] The details of the coating solutions used in this example and comparative example are described below. These were used in Examples 1-6 and Comparative Examples 1-6, and are shown in Table 1.
[0078] [Resin containing an oxazoline group (A)] As a resin containing oxazoline groups, a commercially available water-soluble oxazoline group-containing acrylate ("Epocross® WS-300" manufactured by Nippon Shokubai Co., Ltd.; solid content 10%) was prepared. The amount of oxazoline groups in this resin was 7.7 mmol / g.
[0079] [Acrylic resin (B)] As the acrylic resin, we prepared a 25% by mass emulsion of a commercially available acrylic acid ester copolymer ("Movinyl® 7980" manufactured by Nichigo-Movinyl Co., Ltd.).
[0080] [Urethane resin (C)] As the urethane resin, a commercially available polyester urethane resin dispersion (Mitsui Chemicals, Ltd., "Takelac® W605"; solid content 30%) was prepared. The glass transition temperature (Tg) measured by DSC was 100°C. In addition, the ratio of aromatic or aromatic aliphatic diisocyanate to the total isocyanate component, measured by 1H-NMR, was 55 mol%.
[0081] [Urethane resin (D)] A commercially available polyester urethane resin dispersion (DIC Corporation's "AP201"; solids content 23%) was used as the urethane resin. The glass transition temperature (Tg) measured by DSC was 10°C. The ratio of aromatic or aromatic aliphatic diisocyanate to the total isocyanate component, as measured by 1H-NMR, was 100 mol%.
[0082] [Urethane resin (E-1)] In a four-necked flask equipped with a stirrer, a Liebig condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 143.95 parts by mass of metaxylylene diisocyanate, 25.09 parts by mass of 4,4'-methylenebis(cyclohexyl isocyanate), 28.61 parts by mass of ethylene glycol, 5.50 parts by mass of trimethylolpropane, 12.37 parts by mass of dimethylolpropionic acid, and 120.97 parts by mass of methyl ethyl ketone as a solvent were mixed and stirred at 70°C under a nitrogen atmosphere, and it was confirmed that the reaction solution reached the predetermined amine equivalent. Next, after the reaction solution was cooled to 35°C, 9.14 parts by mass of triethylamine were added to obtain a polyurethane prepolymer solution. Next, 794.97 parts by mass of water were added to a reaction vessel equipped with a homodisperser capable of high-speed stirring, and the temperature was adjusted to 15°C. The polyurethane prepolymer solution was added and dispersed in water while stirring at 2000 min⁻¹. An aqueous amine solution prepared by mixing 22.96 parts by mass of 2-[(2-aminoethyl)amino]ethanol and 91.84 parts by mass of water was then added. Subsequently, an aqueous amine solution prepared by mixing 2.38 parts by mass of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane (trade name: KBM-603, manufactured by Shin-Etsu Chemical Co., Ltd.) and 9.50 parts by mass of water was added to carry out the chain extension reaction. After that, under reduced pressure, methyl ethyl ketone and some of the water were removed to obtain a dispersion containing polyurethane resin (E-1) with a solid content of 25% by mass and an average particle size of 70 nm. The Si content (calculated during preparation) of the obtained polyurethane resin (E-1) was 1200 mg / 1 kg, and the metaxylylene group content (calculated during preparation) was 32% by mass.
[0083] [Urethane resin (E-2)] In a four-necked flask equipped with a stirrer, a Liebig condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 144.69 parts by mass of metaxylylene diisocyanate, 25.21 parts by mass of 4,4'-methylenebis(cyclohexyl isocyanate), 28.76 parts by mass of ethylene glycol, 5.53 parts by mass of trimethylolpropane, 12.43 parts by mass of dimethylolpropionic acid, and 121.59 parts by mass of methyl ethyl ketone as a solvent were mixed and stirred at 70°C under a nitrogen atmosphere, and it was confirmed that the reaction solution reached the predetermined amine equivalent. Next, after the reaction solution was cooled to 35°C, 9.19 parts by mass of triethylamine was added to obtain a polyurethane prepolymer solution. Next, 799.00 parts by mass of water were added to a reaction vessel equipped with a homodisperser capable of high-speed stirring, and the temperature was adjusted to 15°C. The polyurethane prepolymer solution was added and dispersed in water while stirring at 2000 min⁻¹. An amine aqueous solution, a mixture of 24.19 parts by mass of 2-[(2-aminoethyl)amino]ethanol and 96.78 parts by mass of water, was then added to carry out the chain extension reaction. Subsequently, under reduced pressure, methyl ethyl ketone and some of the water were removed to obtain a dispersion containing polyurethane resin (E-2) with a solid content of 25% by mass and an average particle size of 70 nm. The Si content (calculated during the preparation) of the obtained polyurethane resin (E-2) was 0 mg / 1 kg, and the metaxylylene group content (calculated during the preparation) was 32% by mass.
[0084] [Urethane resin (E-3)] In a four-necked flask equipped with a stirrer, a Liebig condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 55.12 parts by mass of 1,3-bis(isocyanatemethyl)cyclohexane, 6.11 parts by mass of triethylene glycol, 162.75 parts by mass of polytetramethylene ether glycol with a number average molecular weight of 2000, 8.19 parts by mass of dimethylolpropionic acid, and 102.15 parts by mass of methyl ethyl ketone as a solvent were mixed and stirred at 70°C under a nitrogen atmosphere, and it was confirmed that the reaction solution reached the predetermined amine equivalent. Next, after the reaction solution was cooled to 35°C, 6.18 parts by mass of triethylamine were added to obtain a polyurethane prepolymer solution. Next, 783.15 parts by mass of water were added to a reaction vessel equipped with a homodisperser capable of high-speed stirring, and the temperature was adjusted to 15°C. The polyurethane prepolymer solution was added and dispersed in water while stirring at 2000 min⁻¹. An aqueous amine solution prepared by mixing 7.49 parts by mass of 2-[(2-aminoethyl)amino]ethanol and 29.97 parts by mass of water was then added. Subsequently, an aqueous amine solution prepared by mixing 4.16 parts by mass of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane (trade name: KBM-603, manufactured by Shin-Etsu Chemical Co., Ltd.) and 16.63 parts by mass of water was added to carry out the chain extension reaction. After that, under reduced pressure, methyl ethyl ketone and some of the water were removed to obtain a dispersion containing polyurethane resin (E-3) with a solid content of 25% by mass and an average particle size of 60 nm. The Si content (calculated during preparation) of the obtained polyurethane resin (E-3) was 2100 mg / 1 kg, and the metaxylylene group content (calculated during preparation) was 0% by mass.
[0085] [Urethane resin (E-4)] In a four-necked flask equipped with a stirrer, a Liebig condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 112.93 parts by mass of metaxylylene diisocyanate, 58.81 parts by mass of 4,4'-methylenebis(cyclohexyl isocyanate), 27.19 parts by mass of ethylene glycol, 5.22 parts by mass of trimethylolpropane, 12.38 parts by mass of dimethylolpropionic acid, and 121.52 parts by mass of methyl ethyl ketone as a solvent were mixed and stirred at 70°C under a nitrogen atmosphere, and it was confirmed that the reaction solution reached the predetermined amine equivalent. Next, the reaction solution was cooled to 35°C, and then 9.15 parts by mass of triethylamine was added to obtain a polyurethane prepolymer solution. Next, 797.80 parts by mass of water were added to a reaction vessel equipped with a homodisperser capable of high-speed stirring, and the temperature was adjusted to 15°C. The polyurethane prepolymer solution was added and dispersed in water while stirring at 2000 min⁻¹. An aqueous amine solution prepared by mixing 21.94 parts by mass of 2-[(2-aminoethyl)amino]ethanol and 87.77 parts by mass of water was then added. Subsequently, an aqueous amine solution prepared by mixing 2.38 parts by mass of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane (trade name: KBM-603, manufactured by Shin-Etsu Chemical Co., Ltd.) and 9.50 parts by mass of water was added to carry out the chain extension reaction. After that, under reduced pressure, methyl ethyl ketone and some of the water were removed to obtain a dispersion containing polyurethane resin (E-4) with a solid content of 25% by mass and an average particle size of 60 nm. The Si content (calculated during preparation) of the obtained polyurethane resin (E-4) was 1200 mg / 1 kg, and the metaxylylene group content (calculated during preparation) was 25% by mass.
[0086] [Gas barrier vinyl alcohol-based resin (F)] As a vinyl alcohol-based resin with gas barrier properties, a commercially available water-soluble vinyl alcohol resin (Nichigo G-Polymer® OKS-8049, manufactured by Nippon Synthetic Chemical Co., Ltd.; powder) Dissolve it in water to prepare a 5% solids aqueous solution.
[0087] [Gas barrier protective layer solution (G: coating liquid 8)] A solution obtained by hydrolyzing tetraethoxysilane with 0.02 mol / L hydrochloric acid is added to a 5 wt% aqueous solution of polyvinyl alcohol resin (PVA) with a degree of saponification of 99% and a degree of polymerization of 2400, in a weight ratio of SiO2 / PVA = 60 / 40 to form a gas barrier protective layer solution (G: coating). Solution 8) was used.
[0088] [Coating liquid 1 for use in the coating layer] The following materials were mixed in the specified proportions to create a coating solution (resin composition for the coating layer). Water 54.40% by mass Isopropanol 25.00% by mass Oxazoline group-containing resin (A) 15.00% by mass Acrylic resin (B) 3.60% by mass Urethane resin (C) 2.00% by mass
[0089] [Coating liquid used for the coating layer 2] The following materials were mixed in the specified proportions to create a coating solution (resin composition for the coating layer). Water 61.96% by mass Isopropanol 25.00% by mass Urethane resin (D) 13.04% by mass
[0090] [Coating liquid 3 for protective layer coating] The following coating agents were mixed to create coating solution 3. Water 30.00% by mass Isopropanol 30.00% by mass Urethane resin (E-1) 40.00% by mass
[0091] [Coating liquid used for protective layer coating 4] The following coating agents were mixed to create coating solution 4. Water 30.00% by mass Isopropanol 30.00% by mass Urethane resin (E-4) 40.00% by mass
[0092] [Coating liquid used for protective layer coating 5] The following coating agents were mixed to create coating solution 5. Water 30.00% by mass Isopropanol 30.00% by mass Urethane resin (E-2) 40.00% by mass
[0093] [Coating liquid used for protective layer coating 6] The following coating agents were mixed to create coating solution 6. Water 30.00% by mass Isopropanol 30.00% by mass Urethane resin (E-2) 17.20% by mass Urethane resin (E-3) 22.80% by mass
[0094] [Coating liquid used for protective layer coating 7] The following coating agents were mixed to create coating solution 7. Water 20.00% by mass Isopropanol 10.00% by mass Gas barrier vinyl alcohol-based resin (F) 70.00% by mass
[0095] The following describes the methods for preparing the base films used in each example and comparative example. The base films used in Examples 1-6 and Comparative Examples 1-6 are shown in Table 1.
[0096] (Preparation of base film (without coating layer)) A polyethylene terephthalate resin with an intrinsic viscosity of 0.62 dl / g (30°C, phenol / tetrachloroethane = 60 / 40) was precrystallized, then fully dried, extruded at 280°C using an extruder with a T-die, and rapidly cooled and solidified on a drum with a surface temperature of 40°C to obtain an amorphous sheet. Next, the obtained sheet was stretched 4.0 times longitudinally at 100°C between a heating roll and a cooling roll. The resulting uniaxially oriented film was then guided to a tenter, preheated at 100°C, stretched 4.0 times transversely at 120°C, and heat-treated at 225°C while allowing 6% transverse relaxation to obtain a biaxially oriented polyester film with a thickness of 12 μm.
[0097] (Preparation of base film (with coating layer)) A polyethylene terephthalate resin with an intrinsic viscosity of 0.62 dl / g (30°C, phenol / tetrachloroethane = 60 / 40) was precrystallized, then fully dried, extruded at 280°C using an extruder with a T-die, and rapidly cooled and solidified on a drum at a surface temperature of 40°C to obtain an amorphous sheet. Next, the obtained sheet was stretched 4.0 times longitudinally at 100°C between a heating roll and a cooling roll. Then, one side of the obtained uniaxially oriented film was coated with either coating liquid 1 or coating liquid 2 using the fountain bar coating method. While drying, it was guided to a tenter, preheated at 100°C, stretched 4.0 times transversely at 120°C, and heat-treated at 225°C while allowing 6% transverse relaxation to be performed to obtain a biaxially oriented polyester film with a thickness of 12 μm coated with 0.050 g / m2. A base film with a covering layer was obtained.
[0098] The methods for preparing the inorganic thin film layers used in each example and comparative example are described below. The methods used in Examples 1-6 and Comparative Examples 1-6 are shown in Table 1. (Formation of inorganic thin film layer M-1) As the inorganic thin film layer M-1, aluminum oxide was deposited onto the substrate film layer. The method for depositing aluminum oxide onto the substrate film layer involved setting the film on the unwinding side of a continuous vacuum deposition machine and winding the film through a cooling metal drum. At this time, the pressure of the continuous vacuum deposition machine was reduced to 10⁻⁴ Torr or less, and 99.99% pure metallic aluminum was loaded into an alumina crucible from the bottom of the cooling drum. The metallic aluminum was heated and evaporated, and oxygen was supplied into the vapor to cause an oxidation reaction, causing it to adhere and deposit onto the film, forming a 10 nm thick aluminum oxide film.
[0099] (Formation of inorganic thin film layer M-2) As the inorganic thin film layer M-2, a composite oxide layer of silicon dioxide and aluminum oxide was formed on the substrate film layer by electron beam deposition. Particulate SiO2 (99.9% purity) and A12O3 (99.9% purity) of approximately 3mm to 5mm in size were used as the deposition source. The thickness of the inorganic thin film layer (SiO2 / A12O3 composite oxide layer) in the resulting film (inorganic thin film layer / coating layer-containing film) was 13nm. The composition of this composite oxide layer was SiO2 / A12O3 (mass ratio) = 60 / 40.
[0100] The lamination method for the protective layer used in each example and comparative example is described below. The methods used in Examples 1-6 and Comparative Examples 1-6 are shown in Table 1.
[0101] (Coating of a coating solution onto a vapor-deposited film (lamination of a protective layer)) The coating solution prepared above was applied to the inorganic thin film layer of the obtained vapor-deposited film by gravure roll coating, pre-dried at 110°C, and then fully dried at 190°C to obtain a protective layer. The coating amount after drying was 0.30 g / m². 2 The sample was (Dry). Subsequently, it underwent post-heat treatment at 40°C for 2 days. The coating liquid constituting the protective layer was changed in each example and comparative example as shown in Table 1.
[0102] As described above, laminated films comprising a coating layer, an inorganic thin film layer, and a protective layer were fabricated on a base film and evaluated. Furthermore, laminated structures were fabricated from the obtained laminated films and evaluated. The results are shown in Table 1.
[0103] [Table 1A]
[0104] [Table 1B] [Industrial applicability]
[0105] The present invention provides a laminated film having an inorganic thin film layer and a protective layer in that order on a polyester resin base film layer, which offers excellent resistance to moisture and heat, alcohol resistance, film recovery, and barrier anisotropy, as well as excellent recyclability, as the laminated film and sealant layer can be easily peeled off from the laminate. Moreover, the laminated film of the present invention can ensure stable quality in a wide range of manufacturing conditions and is not limited by materials in processing steps such as printing and lamination, thus offering excellent economy and production stability, and providing a gas barrier film with homogeneous properties.
Claims
1. A laminated laminate comprising a laminated film having an inorganic thin film layer on at least one side of a polyester base film, and a protective layer on the inorganic thin film layer containing a urethane resin having metaxylylene groups and silanol groups, wherein the laminated film satisfies the following requirements (a) to (d), and a sealant layer is laminated on one side of the laminated film, wherein the laminate strength of the laminated laminate is 1 N / 15 mm or more and 2.5 N / 15 mm or less, and the water-soaked laminate strength after boiling sterilization treatment in 95°C hot water for 2 hours is 1 N / 15 mm or less. (a) The substrate film and the inorganic thin film layer are adjacent to each other. (b) The ratio B / A of the water vapor permeability A when water vapor permeates from the substrate film side to the water vapor permeability B when water vapor permeates from the protective layer side under 40°C × 90% RH conditions is 2.0 or less. (c) The ratio (P2 / P1) of the peak intensity (P1) with an absorption maximum in the region of 1530 ± 10 cm⁻¹ in the total reflection infrared absorption spectrum of the protective layer to the peak intensity (P2) with an absorption maximum in the region of 1530 ± 10 cm⁻¹ on the surface of the protective layer after immersing the laminated film in 95°C hot water for 10 minutes, and then applying and peeling off tape from the surface of the protective layer, is 0.7 or more. (d) The ratio (P2 / P1) of the peak intensity (P1) with an absorption maximum in the region of 1530 ± 10 cm⁻¹ in the total reflection infrared absorption spectrum of the protective layer to the peak intensity (P2) with an absorption maximum in the region of 1530 ± 10 cm⁻¹ on the surface of the protective layer after immersing the laminated film in 99% ethanol for 1 hour, and then applying and peeling off tape from the surface of the protective layer, is 0.7 or greater.
2. The oxygen permeability of the aforementioned laminated film at 23°C × 65% RH is 10 ml / m². 2 The laminate according to claim 1, characterized in that it is d·MPa or less.
3. The laminate according to claim 1 or 2, characterized in that the amount of metaxylylene groups in the urethane resin having metaxylylene groups contained in the protective layer is 12 to 33% by mass, and the amount of silanol groups is 700 to 1700 mg per kg of the resin constituting the polyurethane resin, as the amount of Si elements contained in the silanol groups.
4. The laminate according to any one of claims 1 to 3, wherein the inorganic thin film layer is an aluminum oxide layer or a layer of a composite oxide of silicon oxide and aluminum oxide.
Citation Information
Patent Citations
Anchor to be driven into metal material
JP1980060708A
High adhesion gas barrier transparent laminate, packing material and package
JP2000043182A
Transparent barrier film, and lamination material and package container employing the film
JP2000167973A
Coating composition and laminate
JP2019085511A
Polyurethane dispersion and polyurethane laminate
WO2015016069A1